The socio-economic assessment to evaluate the potentiality of developing the rural community in Upper Egypt - Walid Sallam; Osama Ahmed (International Journal of Food and Agricutural Economics, 2020)
This study evaluates the agricultural interventions related to productivity enhancement that may provide solutions to improve smallholder farmers' incomes. By applying Cost-Benefit Analysis (CBA) and conducting risk analysis using the Monte Carlo simulation technique for the proposed agricultural interventions, this paper evaluates the agricultural interventions in rural communities in Upper Egypt aimed at addressing the current challenges by moving from traditional farming to conservation agricultural. Results indicate that the interventions proposed are viable and have high positive socio-economic impacts on the farmers' livelihoods. The interventions will increase job opportunities in the target regions. Also, a very low probability of negative returns isshown. The probability of negative returns to the socio-economy aspects becomes almost zero when we add the economic benefit to society.
Keywords: C02; C15; C53; C87; Q12; Q13; 330; agricultural interventions; increase farm productivity; improve livelihood; cost-benefit analysis